2004
DOI: 10.1038/sj.bjc.6601525
|View full text |Cite
|
Sign up to set email alerts
|

Randomised trial of a decision aid and its timing for women being tested for a BRCA1/2 mutation

Abstract: The aim of the study was to evaluate the impact of a decision aid (DA) and its timing in women being tested for a BRCA1/2 mutation. Women with and without a previous history of cancer were included after blood sampling for genetic testing. The DA consisted of a brochure and video providing information on screening and prophylactic surgery. To evaluate the impact of the DA, women were randomised to the DA group (n ¼ 184), receiving the DA 2 weeks after blood sampling, or to the control group (n ¼ 184). To evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
87
0
13

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(103 citation statements)
references
References 31 publications
3
87
0
13
Order By: Relevance
“…Several studies suggest using cancer genetic testing decision aids before testing to better inform patients about testing and to assure that they have more accurate risk perceptions. [115][116][117][118] An example of a decision aid used before cancer genetic testing is the computer program "Breast Cancer Risk and Genetic Testing," which is a CD-ROM-based program designed to educate women about breast cancer, heredity, and the benefits and limitations of genetic testing. Users reported that this program was easy to use and provided beneficial educational information before the genetic counseling session, thus allowing the genetic counselors to spend more time discussing specific individual risks and specific psychological concerns.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies suggest using cancer genetic testing decision aids before testing to better inform patients about testing and to assure that they have more accurate risk perceptions. [115][116][117][118] An example of a decision aid used before cancer genetic testing is the computer program "Breast Cancer Risk and Genetic Testing," which is a CD-ROM-based program designed to educate women about breast cancer, heredity, and the benefits and limitations of genetic testing. Users reported that this program was easy to use and provided beneficial educational information before the genetic counseling session, thus allowing the genetic counselors to spend more time discussing specific individual risks and specific psychological concerns.…”
Section: Discussionmentioning
confidence: 99%
“…Original study aims and detailed methods have been published elsewhere [21,22]. Questionnaires were sent at baseline, T1, that is after blood sampling to test for a BRCA1/2 mutation, at T2, 4 weeks after blood sampling, at T3, 2 weeks after a positive test result and at T4, 3 months after a positive test result.…”
Section: Methodsmentioning
confidence: 99%
“…Questionnaires were sent at baseline, T1, that is after blood sampling to test for a BRCA1/2 mutation, at T2, 4 weeks after blood sampling, at T3, 2 weeks after a positive test result and at T4, 3 months after a positive test result. Half of the women received a video and brochure [21], dealing with the decision between prophylactic surgery or screening for breast/ovarian cancer, 2 weeks after the blood sample, together with a follow-up questionnaire to evaluate this information. The outcome measures have been decribed in full detail [21,22].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Various interventions aimed at increasing patient knowledge have been shown to be effective. [19][20][21][22][23][24][25] That said, there are few educational interventions focusing on hereditary breast cancer that target physicians or trainees. 26 Here, we report an evaluation of an interactive web-based genetics curriculum for PCPs using announced standardized patient (SP) visits.…”
Section: Introductionmentioning
confidence: 99%